2013
DOI: 10.4056/sigs.3797438
|View full text |Cite
|
Sign up to set email alerts
|

Permanent draft genome sequences of the symbiotic nitrogen fixing Ensifer meliloti strains BO21CC and AK58

Abstract: Ensifer (syn. Sinorhizobium) meliloti is an important symbiotic bacterial species that fixes nitrogen. Strains BO21CC and AK58 were previously investigated for their substrate utilization and their plant-growth promoting abilities showing interesting features. Here, we describe the complete genome sequence and annotation of these strains. BO21CC and AK58 genomes are 6,985,065 and 6,974,333 bp long with 6,746 and 6,992 genes predicted, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…However, several strains of these rhizobial species do not possess the ability to induce nodule formation (van Rhijn and Vanderleyden, 1995). Probably due to this heterogeneous life style (both free-living and symbiont) rhizobia have large genomes, often composed by several replicative elements (a chromosome, plus additional elements as chromids, megaplasmids, or plasmids) (Harrison et al, 2010;Pini et al, 2011;Black et al, 2012;Galardini et al, 2013a).…”
Section: Rhizobium Genetic Resources Host Specificity and Diversitymentioning
confidence: 99%
“…However, several strains of these rhizobial species do not possess the ability to induce nodule formation (van Rhijn and Vanderleyden, 1995). Probably due to this heterogeneous life style (both free-living and symbiont) rhizobia have large genomes, often composed by several replicative elements (a chromosome, plus additional elements as chromids, megaplasmids, or plasmids) (Harrison et al, 2010;Pini et al, 2011;Black et al, 2012;Galardini et al, 2013a).…”
Section: Rhizobium Genetic Resources Host Specificity and Diversitymentioning
confidence: 99%
“…Recent reports have shown that there are only two genes essential for growth in minimal media and soil encoded in the S. meliloti chromid [ 32 ], even though the chromid harbours many genes shared by all sequenced strains of S. meliloti species. Moreover, S. meliloti has several genomes sequenced to date [ 23 , 30 , 33 39 ] and the potential for biotechnological and agricultural applications, which could benefit from this analysis. At the comparative genomics level, different strains show quite a high level of variation.…”
Section: Introductionmentioning
confidence: 99%
“…The sequence of the S. meliloti AK21 genome has not yet been published, albeit Eckhardt lysis analysis revealed the presence of four replicons, three large ones probably corresponding to the chromosome, pSymA and pSymB, and a 120 kb-length plasmid (Ibragimova et al 2006 ; M. Bazzicalupo personal communication). It is known that other sequenced strains of S. meliloti present a genomic organization similar to Rm1021 (Galardini et al 2011 ) which was annotated with 6,292 genes distributed in the three replicons: 3,429 genes in the chromosome; 1,293 genes in pSymA; and 1,570 genes in pSymB (Galibert et al 2001 ). We detected 365 protein-coding genes differing between the two strains (equivalent to 5.8% of the annotated Rm1021 genome, Additional file 1 ), most of which were absent from or markedly different in S. meliloti AK21, with only one of these genes displaying a lower signal intensity in Rm1021 (SMa1073, 89% identity to an ATP-binding protein).…”
Section: Resultsmentioning
confidence: 99%
“…S. meliloti is found in many different soil environments around the world, suggesting that this species has broad metabolic adaptation capabilities (Souza et al 1992 ; Paffetti et al 1996 ; Jebara et al 2001 ; Roumiantseva et al 2002 ; Biondi et al 2003 ; Giuntini et al 2005 ; Bailly et al 2007 ; Jones et al 2007 ; Stiens et al 2008 ; Schneiker-Bekel et al 2011 ). Investigations of genome dynamics have been carried out at the intra- and interspecies levels in recent years in intensive studies of natural isolates of related rhizobia, discriminating between core and accessory genes (Guo et al 2009 ; Galardini et al 2011 , 2013a , b ; Bailly et al 2011 ; Epstein et al 2012 ; Sugawara et al 2013 ). The complete annotated genome sequence of S. meliloti isolated from diverse soil types (agricultural fields, contaminated soils,…) and continents (1021, SM11, BL225C, AK83, GR4, Rm41) can now be obtained from databases (Galibert et al 2001 ; Schneiker-Bekel et al 2011 ; Galardini et al 2011 ; Martínez-Abarca et al 2013 ), and several other draft genomes are also available (Galardini et al 2013a , b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation